Pengembangan Ekonomi Kreatif Wisata Religi Makam Sunan Muria Kudus - Aryanti Muhtar Kusuma; Alva Nailul Varokh (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2023)
This study aims to analyse creative economy development of the religious tourism Makam Sunan Muria Kudus. This type of research is qualitative research with a field research approach. Methods of data collection by interviews, observation, use of documents, and triangulation. The subjects of this research are the government, intellectuals, and business actors in the area of Makam Sunan Muria Kudus. After the data is collected, the data is analysed by reducing data, presenting data, and verifying data. Based on the results of the research that has been carried out, it shows that the development of the creative economy that has been examined includes several activities such as crafts, fashion, and culinary. The efforts of business actors in developing the creative economy are to create jobs, increase income, and be consistent in running a business. The government's role in efforts to develop the creative economy is by improving the quality of human resources, holding socializations on the economy and employment, bringing in experts, assisting in product promotions, and providing capital loans. The role of intellectuals in efforts to develop the creative economy is to provide creative support and freedom to business actors, maintain infrastructure such as kiosks, and cooperate with BNI bank to provide capital loans.